Sex Differences in the Number and Size of Motoneurons Innervating Rat Medial Gastrocnemius Muscle. (26th April 2013) - Mierzejewska‐Krzyżowska, B.; Bukowska, D.; Taborowska, M.; Celichowski, J.
Summary The sex differences in the number and morphometric parameters of motoneurons in motor nuclei are poorly known. The aim of this study was to determine the differences in the number and size of alpha and gamma motoneurons of the medial gastrocnemius (MG) muscle in male and female Wistar rats. Retrogradely labelled cell bodies of motoneurons of 6 months old animals were studied following a bath of the proximal stump of the transected MG nerve in a horseradish peroxidase solution. The number and soma diameters of male and female MG motoneurons were determined from serial microscopic images of sections. The weight of the brain and spinal cord was on average 17% higher in males than in females. The mean number of motoneurons was 13% higher in males than in females and amounted to 94 and 83 motoneurons, respectively. In each case, the average soma diameters and cross‐section areas of motoneurons in motor nucleus were distributed bimodally: motoneurons smaller than 27.5 μm in diameter were recognized as gamma and greater ones as alpha motoneurons. In males, the motor nucleus contained on the average 66 alpha motoneurons, whereas in females, 56 alpha motoneurons, that is the mean number of alpha motoneurons was 17% higher in males. Moreover, the soma diameters of gamma and alpha motoneurons were significantly bigger in males and the difference amounted 9 and 6%, respectively. It is concluded that the number as well as size of alpha and size of gamma motoneurons in the MG motor nucleus are greater in males.